2010
DOI: 10.1002/jmor.10886
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive histology of Tomeurus gracilis Eigenmann, 1909 (Teleostei: Atherinomorpha: Poeciliidae) with comments on evolution of viviparity in atherinomorph fishes

Abstract: Tomeurus gracilis is a species long considered pivotal in understanding the evolution of livebearing in atherinomorph fishes. Tomeurus gracilis is a zygoparous or embryoparous poeciliid: internal fertilization is followed by females laying fertilized eggs singly or retaining fertilized eggs until or near hatching. Tomeurus was hypothesized as the sister group of the viviparous poeciliids until it was proposed as a close relative of a derived viviparous poeciliid, Cnesterodon, hence nested among viviparous taxa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
20
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 31 publications
2
20
0
Order By: Relevance
“…The histological analysis showed that the testicular structure and spermatogenesis of the restricted spermatogonial testis type of P. mexicana are similar to these described in other poeciliids such as G. affinis holbrooki (Fraile et al, 1992), Poecilia sphenops, P. latipinna (Grier, 1975;Grier et al, 1980;, P. reticulata (Billard, 1969;Pandey, 1969;Vaupel, 1929), and Tomeurus gracilis (Parenti, LoNostro, & Grier, 2010). This testis type has been described not only in poeciliids, but in all members of the orders Atheriniformes, Cyprinodontiformes, and Beloniformes (Parenti & Grier, 2004).…”
Section: Discussionsupporting
confidence: 70%
“…The histological analysis showed that the testicular structure and spermatogenesis of the restricted spermatogonial testis type of P. mexicana are similar to these described in other poeciliids such as G. affinis holbrooki (Fraile et al, 1992), Poecilia sphenops, P. latipinna (Grier, 1975;Grier et al, 1980;, P. reticulata (Billard, 1969;Pandey, 1969;Vaupel, 1929), and Tomeurus gracilis (Parenti, LoNostro, & Grier, 2010). This testis type has been described not only in poeciliids, but in all members of the orders Atheriniformes, Cyprinodontiformes, and Beloniformes (Parenti & Grier, 2004).…”
Section: Discussionsupporting
confidence: 70%
“…Among papers that have appeared in the Journal of Morphology are several "firsts" that warrant mention. These include the following: one of the Grove and Wourms, 1991 Follicular placenta Heterandria formosa (Poeciliidae) Grove and Wourms, 1994 Follicular placenta Heterandria formosa (Poeciliidae) Hollenberg and Wourms, 1994 Trophotaeniae, matrotrophy Goodeidae Jollie and Jollie, 1964a Pregnant ovarian follicle Lebistes reticulatus (Poeciliidae) Jollie and Jollie, 1964b Follicular placenta Lebistes reticulatus (Poeciliidae) Kokkala and Wourms, 1994 Trophotaenial placenta Goodeidae Knight et al, 1985 Follicular placenta, development Anableps (Anablepidae) Kwan et al, 2015 Follicular placenta Poeciliopsis (Poeciliidae) Lombardi and Wourms, 1985a Trophotaenial placenta Ameca splendens (Goodeidae) Lombardi and Wourms, 1985b* Trophotaenial placenta Ameca splendens (Goodeidae) Lombardi and Wourms, 1988 Placental function, matrotrophy Ameca splendens (Goodeidae) Meisner and Burns, 1997 Specializations for matrotrophy Hemiramphidae Mendoza, 1937 Trophotaenial resorption Goodeidae Mendoza, 1956 Trophotaeniae and ovary Hubbsina turneri (Goodeidae) Mendoza, 1958 Specializations for matrotrophy Goodea luitpoldii (Goodeidae) Mendoza, 1972 Trophotaeniae Xenotoca eiseni (Goodeidae) Parenti et al, 2010 Reproductive histology Tomeurus gracilis (Poeciliidae) Schindler and de Vries, 1986 Trophotaeniae Girardinichthys viviparus (Goodeidae) Schindler and de Vries, 1988a Specializations for matrotrophy Jenynsia lineata (Anablepidae) Turner, 1933a Viviparity Goodeidae Turner, 1936 Trophotaeniae Parabrotula dentiens (Brotulidae) Turner, 1937 Trophotaeniae Goodeidae Turner, 1938a Ovarian viviparity, matrotrophy Cymatogaster aggregatus (Embiotocidae) Turner, 1938b Specializations for matrotrophy Anableps anableps Turner, 1940a Specializations for matrotrophy Jenynsia (Anablepidae) Turner, 1940b Specializations for matrotrophy Anablepidae Turner, 1940c Specializations for matrotrophy Poeciliidae Turner, 1940d Specializations for matrot...…”
Section: Role Of the Journal Of Morphologymentioning
confidence: 99%
“…Among living fish (non-tetrapod vertebrates) internal fertilization is mostly effected by copulatory structures representing modifications of the pelvic fins (chondrichthyans 9 ) or anal fins (the gonopodium of some teleost fishes 10,11 ). The discovery in arthrodiran 3 and ptyctodont placoderms 2,4 of copulatory structures (claspers) originally 3, 12 but incorrectly 4 interpreted as modified pelvic fins implied that any placoderms lacking pelvic appendages would have also lacked claspers, and therefore reproduced externally by spawning.…”
mentioning
confidence: 99%
“…The implied loss of bony claspers and implied reversion to external fertilisation in crown gnathostomes appears heterodox: loss of internal fertilization and acquisition of external fertilization is not widely accepted, at least in vertebrates 1,11 although it could have happened multiple times in invertebrates 24 . The shared, unique morphology and post-pelvic position of claspers in all placoderms is more consistent with a single origin, and thus represents a potential synapomorphy supporting placoderm monophyly 25 .…”
mentioning
confidence: 99%